The relationship between individual organizational and interpersonal factors and tacit knowledge sharing with usage the mediator - Alsondos, lbrahim Abu (2014)
The main focus of this study is twofold. Firstly, the thesis attempts to examine the direct relationship between individual (individual attitude, organizational commitment, and knowledge self-efficacy), organizational (organizational climate, management support, reward system and organizational structure), and interpersonal (interpersonal trust and social network) factors, and tacit knowledge sharing. Secondly, it is to examine the mediating effect of information and communication technology (ICT) usage on the relationship between individual, organizational and interpersonal factors, and tacit knowledge sharing. A total of 400 questionnaires were distributed to the technical staff of ICT sector in Jordan. Out of 400, only 375 questionnaires were returned. However, only 365 were usable for further analysis, representing a response rate of 92.75%. Hypotheses for direct relationships were tested using multiple regression, while the mediating effect were tested using the Preacher and Hayes analyses. Results indicated that individual attitude, knowledge self-efficacy, organizational climate, organizational structure, management support and interpersonal trust were significantly related to tacit knowledge sharing. However, the mediating analysis showed that ICT usage only partially mediated the relationship between knowledge self-efficacy, organizational climate, organizational structure and interpersonal trust, and tacit knowledge sharing. The current research have several implications. Knowledge wise, it provides understanding on the factors that affects tacit knowledge sharing. Practise wise, it suggests to managers that they should focus on providing the right management support, organizational structure and climate for sharing tacit knowledge. In addition, any practices that could promote organizational commitment, knowledge self-efficacy and interpersonal trust should also be implemented. The use of ICT should also be enforced so as to facilitate tacit knowledge sharing. Besides that, suggestions were also made for further research to be conducted the exploration of the variables tested in this study on other settings, and with different sample frames, in order to achieve a more robust finding towards a better understanding of the role of individual, interpersonal and organizational factors on tacit knowledge sharing